2016
DOI: 10.5664/jcsm.5940
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous Positive Airway Pressure on Stroke Rehabilitation: A Pilot Randomized Sham-Controlled Trial

Abstract: Study Objectives: Obstructive sleep apnea (OSA) predicts poor functional outcome after stroke and increases the risk for recurrent stroke. Less is known about continuous positive airway pressure (CPAP) treatment on stroke recovery. Methods: In a pilot randomized, double-blind, sham-controlled trial, adult stroke rehabilitation patients were assigned to auto-titrating or sham CPAP without diagnostic testing for OSA. Change in Functional Independence Measure (FIM), a measure of disability, was assessed between r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…4 Pilot RCTs have evaluated the effect of CPAP on functional and cognitive outcomes, with mixed results. 6,16,18,[20][21][22][23][24] The majority of trials were conducted in stroke rehabilitation units or a limited number of hospitals, with sample sizes ranging from 30 to 252. Our results now suggest that functional and cognitive outcomes are reasonable targets for larger, adequately powered trials of the effectiveness of CPAP in improving stroke outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Pilot RCTs have evaluated the effect of CPAP on functional and cognitive outcomes, with mixed results. 6,16,18,[20][21][22][23][24] The majority of trials were conducted in stroke rehabilitation units or a limited number of hospitals, with sample sizes ranging from 30 to 252. Our results now suggest that functional and cognitive outcomes are reasonable targets for larger, adequately powered trials of the effectiveness of CPAP in improving stroke outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25] If treatment with CPAP is shown to improve stroke outcomes in a larger, adequately powered clinical trial, treatment of SDB may be a viable, cost-efficient intervention strategy to improve stroke recovery. [16][17][18][19][20][21][22][23][24][25] If treatment with CPAP is shown to improve stroke outcomes in a larger, adequately powered clinical trial, treatment of SDB may be a viable, cost-efficient intervention strategy to improve stroke recovery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In cross-sectional analyses, Arzt et al (2005) found that subjects with an AHI of 5-19.9 had lower odds (OR = 0.49) whereas subjects with an AHI ࣙ 20 had higher odds (OR = 3.8) to have suffered a stroke than individuals without OSA (AHI ࣘ 5) after controlling for age, sex, BMI, alcohol consumption, cigarette smoking, hypertension and diabetes. Similarly, a recent double-blind randomized controlled trial comparing CPAP to sham-CPAP treatment of OSA in stroke patients found no significant benefit of CPAP on a functional independence measure aimed at assessing global disability (Khot et al 2016). Likewise, Yaggi et al (2005) reported OSA patients to be at higher risk of stroke compared with OSA-free control subjects [hazard ratio (HR) = 1.97] after controlling for age, sex, race, smoking status, alcohol consumption, BMI, diabetes, hyperlipidaemia, atrial fibrillation and hypertension.…”
Section: Obstructive Sleep Apnoea and Vascular Diseasementioning
confidence: 99%
“…In a longitudinal component consisting of a 4 year follow-up, after controlling for age, sex and BMI, subjects with an AHI between 5 and 19.9 at baseline had lower odds (OR = 0.29) whereas subjects with an AHI ࣙ 20 had higher odds (OR = 3.1) of suffering a first ever stroke compared with subjects with an AHI ࣘ 5, although these differences were not statistically significant. Unfortunately, these two randomized controlled trials (Ryan et al 2011;Khot et al 2016) had relatively small sample sizes and thus were likely to be statistically underpowered to observe an improvement in function. In addition, a stepwise increase in stroke risk and all-cause mortality was observed for increasing OSA severity, with the HR being 1.75 for mild OSA (AHI = 4-12), 1.74 for moderate OSA (AHI = 13-36) and 3.30 for severe OSA (AHI ࣙ 36) compared with individuals with an AHI ࣘ 3.…”
Section: Obstructive Sleep Apnoea and Vascular Diseasementioning
confidence: 99%